Dampak Tindakan Bullying Relasional Terhadap Minat Belajar Siswa - Westri Septiana Nainggolan; Elsa Karolina Damanik; Fatma Tresno Ingtyas; Laurena Ginting (Lembaga Pengembangan Kinerja Dosen, 2025)
Relational bullying is a form of bullying that often occurs in the school environment and has a significant impact on the psychological and academic aspects of students. This research aims to analyze the influence of relational bullying on students’ interest in learning at various levels of education. The research method used is literature review by reviewing 11 relevant national journals indexed by Google Scoler, DOAJ and Sinta, which were published between 2018 and 2024. The results of the study show that relational bullying generally appears in the form of exclusion, spreading gossip, manipulation of social relationships, indirect mockery, and seniority behavior. The impacts caused include a decrease in academic confidence, increased anxiety and depression, loss of study concentration, and low student motivation and participation in class. This condition implies a decrease in learning achievement and student involvement in school activities. Based on the findings, it is concluded that relational bullying has a significant negative effect on students’ interest in learning. Therefore, prevention efforts are needed through the establishment of a positive school climate, strengthening the value of empathy, and the provision of sustainable counseling services to create a safe learning environment and support the development of students.